2009
DOI: 10.1016/j.febslet.2009.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion disassembly requires clathrin‐dependent endocytosis of integrins

Abstract: a b s t r a c tCell migration requires the controlled disassembly of focal adhesions, but the underlying mechanisms remain poorly understood. Here, we show that adhesion turnover is mediated through dynamin-and clathrin-dependent endocytosis of activated b1 integrins. Consistent with this, clathrin and the clathrin adaptors AP-2 and disabled-2 (DAB2) distribute along with dynamin 2 to adhesion sites prior to adhesion disassembly. Moreover, knockdown of either dynamin 2 or both clathrin adaptors blocks b1 integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
189
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(200 citation statements)
references
References 26 publications
7
189
2
2
Order By: Relevance
“…As integrins are a major component of focal adhesions, their removal is an integral part of focal adhesion disassembly. While the protease calpain contributes to this by cleaving focal adhesion proteins like integrins and talin [85], dynamin and CME of active b1 integrins were also shown to be instrumental for this process [72,86]. Proteins of the endocytic machinery like clathrin, AP-2, Dab2 and dynamin2 localize to adhesion sites prior to adhesion disassembly.…”
Section: Focal Adhesion Disassemblymentioning
confidence: 99%
See 1 more Smart Citation
“…As integrins are a major component of focal adhesions, their removal is an integral part of focal adhesion disassembly. While the protease calpain contributes to this by cleaving focal adhesion proteins like integrins and talin [85], dynamin and CME of active b1 integrins were also shown to be instrumental for this process [72,86]. Proteins of the endocytic machinery like clathrin, AP-2, Dab2 and dynamin2 localize to adhesion sites prior to adhesion disassembly.…”
Section: Focal Adhesion Disassemblymentioning
confidence: 99%
“…Proteins of the endocytic machinery like clathrin, AP-2, Dab2 and dynamin2 localize to adhesion sites prior to adhesion disassembly. The importance of CME for focal adhesion disassembly is highlighted by the fact that depletion of dynamin2 blocks b1 integrin internalization leading to impaired focal adhesion disassembly and consequently to defects in cell migration [86]. CME depends on phosphatidylinositol (4,5)bisphosphate [PI(4,5)P 2 ] which is generated by the enzyme PIPK1b and contributes to the recruitment of endocytic proteins like AP-2.…”
Section: Focal Adhesion Disassemblymentioning
confidence: 99%
“…43 Several reports demonstrate a role for NO in clathrin-and dynaminmediated endocytosis and also integrins can be endocytosed by these pathways. [27][28][29]44 NO S-nitrosylates dynamin increasing dynamin oligomerization and GTPase activity, thereby increasing endocytosis. 33 Our results support a role for dynamin in ILK internalization because a specific inhibitor of dynamin activation reversed ILK degradation and localization in endosomes and later in lysosomes, thus proving that NO drives ILK endocytosis to direct ILK to lysosome degradation.…”
Section: Discussionmentioning
confidence: 99%
“…26 Thus, we sought to investigate whether NO Endocytosis of integrins and associated proteins can be accomplished by chlatrin-dependent, caveolae-dependent, and noncaveolae-mediated pathways. [27][28][29] The first 2 processes rely on the GTPase dynamin for the scission of endocytic intermediates to generate early endosomes. 30 Previous studies have demonstrated that NO can stimulate endocytosis by S-nytrosilation of dynamin.…”
Section: No Triggers Ilk Endocytosis Through a Dynamin-dependent Pathwaymentioning
confidence: 99%
“…The lipid second messengers play an important role in this retraction process, with PIP 2 levels remaining high at the cell front to ensure that adapters such as talin are recruited to facilitate the adapter-mediated endocytosis of integrins (Chao et al 2010a). Conversely, to prevent the recruitment of integrin adaptors involved in adhesion site initiation and assembly at the rear of the cell, such as ILK and kindlin, the levels of PIP 3 are kept low (Chao and Kunz 2009;Ezratty et al 2009;Chao et al 2010b). …”
Section: Integrin-mediated Migrationmentioning
confidence: 99%